Rancang Bangun Prototipe Pemantau Temperatur Ruang Penyimpanan Anak Timbangan Standar di Unit Metrologi Legal Kabupaten Bandung Barat - Firmansyah, Vera; Nuriska, Fanny; Mulyana, Teddy; Firmansyah, Dudi Adi; Yasri, Budi; Muslim, Azis; Gianto; Gunawan T.W, Nandang; Sutanto, Willi (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2024)
The Legal Metrology Unit (UML) is a unit that carries out metrological activities in the Regency/City. UML has a vital role in achieving a well-measured market. These metrological activities include calibration and re-calibration and metrological supervision activities. One of UML's efforts to support these activities is to maintain the working standards it has, in this case, reference weights. In addition to purchasing existing measuring instruments with four sensors at once being very expensive, prototyping is the leading choice because it can be developed according to needs. This study created a prototype for monitoring the room conditions of the reference weight storage cabinet. This prototype uses four sensors integrated with a microcontroller to measure temperature simultaneously. The testing process for the prototype began with testing the temperature sensor with a standard thermocouple and water bath. Furthermore, the prototype will be tested with a standard thermohygrometer measuring instrument. The test results of the prototype for accuracy have a range of 94%-98%, precision of 97%-98%, and an error of 2%-4%. Meanwhile, the results of the measurement uncertainty of the prototype for the morning are by the provisions in the range of 0.37 °C-0.46 °C, and in the afternoon, they do not comply with the requirements, namely in the range of 0.38°C-0.61 °C.